Capitalismo e hidronegócio : impactos socioambientais da UHE Sinop nos projetos de assentamento no norte de Mato Grosso - Silva, Clodoaldo Clemente da (2023)
Due to their enviable flow, the Amazonian rivers have attracted the attention of capitalized groups that, through the consent of the State, have appropriated their waters. The discourse of progress and economic development has advanced the agricultural frontier through agribusiness into the Amazon. The materialization of the hydrobusiness has been constituted in the construction of hydroelectric plants throughout Brazil and especially in the Teles Pires River basin in a complex of hydroelectric plants with the absence of a study of synergistic impact. Even before its operation, the Sinop Hydroelectric Plant already caused social impacts to families that inhabited the region that would serve as a reservoir. In particular, the families of the Settlement 12 de Outubro in Cláudia -MT and Gleba Mercedes in Sinop - MT who had a large part of their land flooded, in a process of deterritorialization, and with that their dreams and their identities shaken having to start their lives over again , if (re)territorialized, in other places under other forms. The environmental impacts were already felt in the first months of its operation, when its gates were closed, killing tons of fish in the Teles Pires River. Current legislation, law (3.824/60), regarding the removal of 100% of the vegetation was not complied with. Its operating license, which should have been issued by the competent federal agency, ended up being issued by a state agency. Even after all these problems and irregularities, the hydroelectric plant belonging to the French State continues to operate and the Gleba Mercedes families have still not been properly compensated for their land. The practices of building hydroelectric power plants throughout Brazil are once again repeated, now in the north of Mato Grosso.